2021
DOI: 10.3390/mi12121523
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Photoelectrochemical DNA Biosensors Based on TiO2@Carbon Dots@Black Phosphorous Quantum Dots

Abstract: In this work, carbon dots (CDs) and black phosphorus quantum dots (BPQDs) were used to decorate titanium dioxide to enhance the photoelectrochemical (PEC) properties of the nanocomposites (TiO2@CDs@BPQDs), and the modified nanocomposites were used to sensitively detect DNA. We used the hydrothermal method and citric acid as a raw material to prepare CDs with good dispersion and strong fluorescence properties. BPQDs with a uniform particle size were prepared from black phosphorus crystals. The nanocomposites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This biosensor provided a label-free detection of small biomolecules. The BP nanoparticles were used as fluorescent biosensing for the detection of DNA [179,180]. BP nanoparticles were synthesized from red phosphorus using high-pressure phase transformation.…”
Section: Black Phosphorus (Bp)mentioning
confidence: 99%
“…This biosensor provided a label-free detection of small biomolecules. The BP nanoparticles were used as fluorescent biosensing for the detection of DNA [179,180]. BP nanoparticles were synthesized from red phosphorus using high-pressure phase transformation.…”
Section: Black Phosphorus (Bp)mentioning
confidence: 99%
“…Similarly, Song and colleagues illustrated the assembly of photoelectrochemical DNA‐based biosensors prepared using carbon dots (CDs), TiO 2 , and black phosphorus quantum dots (BPQDs). [ 95 ] The obtained results demonstrated that BPQDs and CDs possessed unique optical properties when combined with TiO 2 to develop a TiO 2 @CDs@BPQDs hybrid nanostructure, and exhibited much better PEC‐enabled biosensing properties towards DNA detection. [ 95 ] Consequently, the low detection limit of 8.39 nM along with a wide detection range, improved the sensitivity, and specificity that could be recorded.…”
Section: Tio2 Photocatalyst‐enabled Sensingmentioning
confidence: 99%
“…[ 95 ] The obtained results demonstrated that BPQDs and CDs possessed unique optical properties when combined with TiO 2 to develop a TiO 2 @CDs@BPQDs hybrid nanostructure, and exhibited much better PEC‐enabled biosensing properties towards DNA detection. [ 95 ] Consequently, the low detection limit of 8.39 nM along with a wide detection range, improved the sensitivity, and specificity that could be recorded. In one study, the preparation of a PEC sensor using TiO 2 P25 NPs has been reported by Mokhtar and co‐workers.…”
Section: Tio2 Photocatalyst‐enabled Sensingmentioning
confidence: 99%
“…CQDs and other quantum dots, such as silicon, phosphorous, germanium, or from compound semiconductor materials, such as CdSe, CdTe, and PbS have been discovered and exhibits strong PLQY, and tuneable photoluminescence in general. However, the high cost, toxic nature, complex method of preparation and use of hazardous precursors in the synthetic procedure limit their mass production and use in practical applications [49,50] …”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost, toxic nature, complex method of preparation and use of hazardous precursors in the synthetic procedure limit their mass production and use in practical applications. [49,50] For the synthesis of CQDs, two alternative approaches, "topdown" and "bottom-up," have generally been used, depending on the type of source or precursor materials. [23] The "top-down" synthetic process involves employing laser ablation, arc discharge, ultrasonic treatment, and electrochemical techniques to break down bigger carbon structures such as graphite, carbon nanotubes (CNTs), and nano diamonds into CQDs.…”
Section: Introductionmentioning
confidence: 99%